2018
DOI: 10.18178/ijssh.2018.v8.932
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sustainable Consumption Behavior: An Examination of Consumption Values, PCE Environmental Concern and Environmental Knowledge

Abstract: One of the proposed concept in handling environmental problems by involving consumers' participation is sustainable consumption. It is suggested that consumers as the end users can contribute a significant impact in sustainable development through their choices and behaviors as the purchasers and main end-users. But, they need help to form their consumption habit and behavior. Therefore, this study tries to discover what factors can encourage sustainable consumption behavior of Indonesian young adults.A quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Thus, favorable expectations about the future of the environment serves to boost the feeling of responsibility and empowerment, which consequently lead to a more efficient electricity usage. This finding is in line with those of previous studies, which found that positive affect and concern about the environment trigger pro-environmental behavior (Rizkalla, 2018;White & Habib, 2018;Wilson & Dowlatabadi, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, favorable expectations about the future of the environment serves to boost the feeling of responsibility and empowerment, which consequently lead to a more efficient electricity usage. This finding is in line with those of previous studies, which found that positive affect and concern about the environment trigger pro-environmental behavior (Rizkalla, 2018;White & Habib, 2018;Wilson & Dowlatabadi, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Also, consumers that are environmentally concerned are highly related to having subjective environmental knowledge (SEK). For instance, Rizkalla (2017) found that an increase in the concerns or issues regarding the environment increases environmental knowledge. Also, according to (Pagiaslis & Krontalis, 2014) environmental concern significantly affects SEK and helps consumers in having a certain amount of information towards preserving the environment.…”
Section: Literature Reviews and Building Of Hypothesesmentioning
confidence: 99%
“…The KV provides the relevant information to the individual regarding product use, attributes, and functionality, thus encouraging sustainable consumption behavior. This insight allows the consumers to base their decision on knowledge objectively, thus following the long-standing tradition of consumption patterns ( Rizkalla, 2018 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%